Callosal Interhemispheric Communication in Mild Traumatic Brain Injury: A Mediation Analysis on WM Microstructure Effects - Chung, Sohae; Bacon, Tamar; Rath, Joseph F.; Alivar, Alaleh; Coelho, Santiago; Amorapanth, Prin; Fieremans, Els; Novikov, Dmitry S.; Flanagan, Steven R.; Bacon, Joshua H.; Lui, Yvonne W. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Because the corpus callosum connects the left and right hemispheres and a variety of WM bundles across the brain in complex ways, damage to the neighboring WM microstructure may specifically disrupt interhemispheric communication through the corpus callosum following mild traumatic brain injury. Here we use a mediation framework to investigate how callosal interhemispheric communication is affected by WM microstructure in mild traumatic brain injury.MATERIALS AND METHODS: Multishell diffusion MR imaging was performed on 23 patients with mild traumatic brain injury within 1 month of injury and 17 healthy controls, deriving 11 diffusion metrics, including DTI, diffusional kurtosis imaging, and compartment-specific standard model parameters. Interhemispheric processing speed was assessed using the interhemispheric speed of processing task (IHSPT) by measuring the latency between word presentation to the 2 hemivisual fields and oral word articulation. Mediation analysis was performed to assess the indirect effect of neighboring WM microstructures on the relationship between the corpus callosum and IHSPT performance. In addition, we conducted a univariate correlation analysis to investigate the direct association between callosal microstructures and IHSPT performance as well as a multivariate regression analysis to jointly evaluate both callosal and neighboring WM microstructures in association with IHSPT scores for each group.RESULTS: Several significant mediators in the relationships between callosal microstructure and IHSPT performance were found in healthy controls. However, patients with mild traumatic brain injury appeared to lose such normal associations when microstructural changes occurred compared with healthy controls.CONCLUSIONS: This study investigates the effects of neighboring WM microstructure on callosal interhemispheric communication in healthy controls and patients with mild traumatic brain injury, highlighting that neighboring noncallosal WM microstructures are involved in callosal interhemispheric communication and information transfer. Further longitudinal studies may provide insight into the temporal dynamics of interhemispheric recovery following mild traumatic brain injury.aCR/sCR/pCRanterior/superior/posterior corona radiataaIC/pIC/rICanterior/posterior/retrolenticular limb of the internal capsuleCCcorpus callosumCgcingulum (cingulate gyrus)Chcingulum (hippocampus)Daintra-axonal diffusivityDe‖extra-axonal axial diffusivityDe⊥extra-axonal radial diffusivityDKIdiffusional kurtosis imagingƒaxonal water fractionFAfractional anisotropygCC/bCC/sCCgenu/body/splenium of corpus callosumIHSPTinterhemispheric speed of processing taskLleftLVFleft visual fieldMD/AD/RDmean/axial/radial diffusivitiesMK/AK/RKmean/axial/radial kurtosisMTBImild traumatic brain injuryRrightRTreaction timeRVFright visual fieldSFOFsuperior fronto-occipital fasciculusSLFsuperior longitudinal fasciculusSMstandard modelTBSSTract-Based Spatial Statistics